Toleransi Beragama dalam Al-Qur`an (Studi Komparatif Atas Tafsir Ibn Katsîr dan Tafsir Al-Misbâh) - Khoerul Musafak; Abd. Muid Nawawi; Muh. Adlan Nawawi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Diversity is a necessity that should be run without rejection. In recent times, diversity comes with a variety of truth claims that lead to the recognition and arrogance of the existence of himself and his group, giving birth to an intolerant attitude. The trigger of the problem is a mistake in capturing the message of tolerance from religion so that its adherents appear with different faces. Based on these problems, researchers are interested in exploring how the interpretation of Ibn Kathir and M. Quraysh Shihab related religious tolerance as well as the implications of the socio-historical background of both on the interpretation. The approach used in this study is qualitative with comparative study method. The data collection technique in the form of literature and observation studies were analyzed in the data collection technique in the form of descriptive analysis with the method of comparative analysis (analytical-comparative method) as for the theory used to strengthen as a surgical research tool is the theory of genetic structuralism of Lucien Goldmann who explained that a work or text is the work of the author in this case the elements as the author of the text as well as historical facts that condition the emergence of such works or texts. The results showed that there are differences in the tendency of interpretation as well as interpretation between Ibn Kathir and M. Quraish Shihab. In general, both agree on how coercion in embracing religion is not allowed, it's just that Ibn Kathir directs the meaning of religious tolerance with applicable restrictions and conditions.